Techno-Economic Optimization of Multistage Membrane Processes with Innovative Hollow Fiber Modules for the Production of High-Purity co2 and ch4 from Different Sources - Abejon-Elias, R (American Chemical Society, 2022)
Within the current climate emergency framework and in order to avoid the most severe consequences of global warming, membrane separation processes have become critical for the implementation of carbon capture, storage, and utilization technologies. Mixtures of CO2 and CH4 are relevant energy resources, and the design of innovative membranes specifically designed to improve their separation is a hot topic. This work investigated the potential of modified polydimethylsiloxane and ionic liquidchitosan composite membranes for separation of CO2 and CH4 mixtures from different sources, such as biogas upgrading, natural gas sweetening, or CO2 enhanced oil recovery. The techno-economic optimization of multistage processes at a real industrial scale was carried out, paying special attention to the identification of the optimal configuration of the hollow fiber modules and the selection of the best membrane scheme. The results demonstrated that a high initial content of CH4 in the feed stream (like in the case of natural gas sweetening) might imply a great challenge for the separation performance, where only membranes with exceptional selectivity might achieve the requirements in a two-stage process. The effective lifetime of the membranes is a key parameter for the successful implementation of innovative membranes in order to avoid severe economic penalties due to excessively frequent membrane replacement. The scale of the process had a great influence on the economic competitiveness of the process, but large-scale installations can operate under competitive conditions with total costs below 0.050 US$ per m(3) STP of treated feed gas.